2018
DOI: 10.1021/acs.inorgchem.8b01326
|View full text |Cite
|
Sign up to set email alerts
|

Influencing the Optoelectronic Properties of a Heteroleptic Iridium Complex by Second-Sphere H-Bonding Interactions

Abstract: The use of a new second-sphere coordination methodology for emission color tuning of iridium complexes is presented. We demonstrate that a complementary H-bonding guest molecule binding through contiguous triple H-bonding interactions can induce a shift in the emission of the iridium complex from green to blue without the need to alter the ligand structure around the metal center, while simultaneously increasing the photoluminescence quantum yield in solution. The association constant for this host-guest inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…We have shown that the seemingly minor change of an S to NH can have significant effects upon the biological action of the molecules. This may relate to changes in conformation of the molecules due to intramolecular hydrogen bond formation . In the case of the iridium complexes, the toxicity trend was reversed, but we were able to observe a dramatic difference in subcellular distribution of the complexes according to the S/NH substitution.…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…We have shown that the seemingly minor change of an S to NH can have significant effects upon the biological action of the molecules. This may relate to changes in conformation of the molecules due to intramolecular hydrogen bond formation . In the case of the iridium complexes, the toxicity trend was reversed, but we were able to observe a dramatic difference in subcellular distribution of the complexes according to the S/NH substitution.…”
Section: Methodsmentioning
confidence: 71%
“…We are currently investigating guanidine‐ and thiourea‐based molecules as components in advanced organic LED materials through formation of luminescent iridium complexes . Iridium complexes themselves are of great interest as potential cancer therapeutics because they generate a 3D scaffold, enabling structural diversity beyond the ‘flatter’ organic molecules or platinum complexes used in cancer therapy; they offer an opportunity for simultaneous imaging due to their rich and tunable luminescence properties; and they offer an opportunity for photogeneration of singlet oxygen within cells .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, studies on Ru II and Os II ‐containing bpy ligands derivatized by nucleobases have been shown to form triple hydrogen bonded heterosynthons within which the emission of the ruthenium center is quenched by the osmium center . Triple hydrogen bonding interactions have also been shown very recently to be able to non‐covalently tune the emission properties of an Ir III ‐based system . Another recent report has also highlighted the ability of hydrogen bonding to facilitate photocatalysis reactions in Ir III complexes .…”
Section: Introductionmentioning
confidence: 99%
“…[10] Triple hydrogen bonding interactions have also been shown very recently to be ablet o non-covalently tune the emission properties of an Ir III -based system. [11] Another recentr eport has also highlighted the ability of hydrogen bonding to facilitate photocatalysis reactions in Ir III complexes. [12] There are fewer reports concerning the incorporation of such centers into functional materials.…”
Section: Introductionmentioning
confidence: 99%